Factors Affecting Oral Hygiene and Tooth Brushing in Preschool Children, Shiraz/Iran - Shaghaghian S; Zeraatkar M (Shiraz University of Medical Sciences, 2017)
Abstract Statement of Problem: Inadequate tooth brushing and inappropriate oral hygiene can lead to dental caries, the most common chronic diseases of childhood with several side effects. Objectives: To evaluate factors affecting on preschool children's oral hygiene and tooth brushing in Shiraz, Iran Materials and Methods: In this cross-sectional study, we selected 453 children registered in Shiraz kindergartens in 2013 by randomized cluster sampling. The children's tooth brushing and oral hygiene were assessed using a reliable and valid questionnaire and Simplified Debris Index (DI-S), respectively. A dental student examined all the children in each kindergarten to determine their DI-S. The relationship between the children's demographic variables and their oral hygiene and tooth brushing status were evaluated. Results: Tooth brushing for 272 children (71.2%) had been started after the age of 2 years. The teeth in 96 children (24.2%) had been brushed lower than once daily. The mean of the children's DI-S was 1.19 ± (0.77). The DI-S of only 126 children (31.8%) was found to be good and very good. After controlling the effect of confounding factors, we found that the children's tooth brushing frequency was significantly associated with the number of children in the family and mothers' employment status. The age at which tooth brushing had been started was significantly associated with the fathers' education. Furthermore, the DI-S was associated with children's age, number of the children in the family, and their mothers' education. Conclusions: Oral hygiene and tooth brushing of the preschool children were not in a desirable status. Interventional procedures, especially educational programs, are recommended for children and their parents. These programs seem to be more necessary for older children, low socioeconomic families, and families with more than one child.